2005
DOI: 10.1111/j.1745-7270.2005.00118.x
|View full text |Cite
|
Sign up to set email alerts
|

Two Human ACAT2 mRNA Variants Produced by Alternative Splicing and Coding for Novel Isoenzymes

Abstract: Acyl coenzyme A:cholesterol acyltransferase 2 (ACAT2) plays an important role in cholesterol absorption. Human ACAT2 is highly expressed in small intestine and fetal liver, but its expression is greatly diminished in adult liver. The full-length human ACAT2 mRNA encodes a protein, designated ACAT2a, with 522 amino acids. We have previously reported the organization of the human ACAT2 gene and the differentiation-dependent promoter activity in intestinal Caco-2 cells. In the current work, two human ACAT2 mRNA v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…However no ACAT-2 mRNA was detected in adult liver (Yao et al,2005), in agreement with previous reports of low levels of ACAT-2 expression in adult human liver compared to foetal liver (cf. also Chang et al, 2000).…”
Section: Genomic Organization and Transcription Of The Human Acat-2 Genesupporting
confidence: 92%
See 3 more Smart Citations
“…However no ACAT-2 mRNA was detected in adult liver (Yao et al,2005), in agreement with previous reports of low levels of ACAT-2 expression in adult human liver compared to foetal liver (cf. also Chang et al, 2000).…”
Section: Genomic Organization and Transcription Of The Human Acat-2 Genesupporting
confidence: 92%
“…Whereas the full length ACAT-2a mRNA encodes a deduced ~60 kDa protein consisting of 522 amino acids, the ACAT-2b and ACAT-2c variants encode proteins of 502 amino acids and 379 amino acids, respectively. ACAT-2b mRNA differs from ACAT-2a mRNA by lacking exon 4, while ACAT-2c mRNA differs from ACAT-2a mRNA by lacking exons 4, 5, and 8, 9 and 10 (Yao et al,2005).…”
Section: Genomic Organization and Transcription Of The Human Acat-2 Genementioning
confidence: 93%
See 2 more Smart Citations
“…The regulatory expression and functional mechanisms of human ACAT1 have been studied [15][16][17][18][19][20][21][22]. For human ACAT2 gene, we have previously reported its genomic organization, the intestinal Caco-2 cell differentiation-dependent promoter activity, and two novel isoforms (named as ACAT2b and ACAT2c) encoded by the alternative-spliced two mRNA variants with reduced enzymatic activities [23,24]. Moreover, it has been reported that ACAT2 is highly expressed in the livers of mice and monkeys [25][26][27].…”
Section: Introductionmentioning
confidence: 99%